Bit and beat are heard as the same: Mapping the vowel perceptual patterns of Greek-English bilingual children. (March 2019) - Georgiou, Georgios P.
Abstract: It has been previously proposed that small native vowel inventories impede the acquisition of foreign language vowels that come from larger inventories. The present study aims to investigate how the already-formed Greek phonological system is modified after the perception of the English vowels in a non-naturalistic environment and to what extent Greek speakers are able to discriminate challenging English vowel contrasts. Also, it aims to examine if learning experience enhances sensitivity to acoustical information of the foreign language vowels. The study relies on the theoretical framework of the Perceptual Assimilation Model-Second Language (PAM-L2). For developing predictions about the perception of the English vowels by Greek speakers, the vowel spaces of both Greek and English native speakers were investigated; 3 native speakers of Greek and 3 native speakers of English produced vowels in their native language. 26 Greek learners of English as a foreign language in Cyprus with an age that varied from 8 to 12 years participated in the perceptual study. Learners were divided into two groups according to their proficiency level in English. The participants took an identification test in order to determine how English vowels were assimilated to the listeners' native phonological categories and then they were tested in an AXB discrimination task in order to investigate to what extent they are able to discriminate English vowel contrasts. The results showed that several pairs of two or more English vowels were assimilated to a single Greek phonological category. Furthermore, the discrimination test showed poor to moderate discrimination accuracy for both groups regarding the English vowel contrasts, yet differences in the discrimination accuracy of the contrasts between the novice and the more advanced group of learners were minimal; only the English/e/-/ɜː/contrast was discriminated slightly better by the advanced learners. Thus, learners with a higher proficiency level did not generally perceive the English vowels better than learners with a lower proficiency level, signifying that perception of foreign language vowels is not merely a matter of amount of exposure to the foreign stimuli. Conclusions are drawn about the interference of native Greek with the learning of English vowels and the acquisition of the foreign language stimuli in a classroom environment. Highlights: Several pairs of English vowels were assimilated to a single Greek vowel category. There was poor to moderate discrimination for specific English vowel contrasts. Sensitivity in acoustical differences was not affected by proficiency level.